Experimental modelling of critical damage obtained in Al–Mg and Al–Mn alloys for both annealed state and previously deformed by ECAP. (15th January 2016) - Luri, R.; Fuertes, J.P.; Luis, C.J.; Salcedo, D.; Puertas, I.; León, J.
Abstract: Assessing the damage produced in plastic deformation processes permits the optimum manner to shape a material that could avoid any cracks from appearing. In this present research work, the absolute critical damage in the following aluminium alloys: AA5754, AA5083 and AA3103 is to be determined. In order to do this, compression tests between plane-shape dies will be performed for the abovementioned alloys at a temperature range which varies from 25 °C to 300 °C and using Cockroft–Latham's prediction model. Furthermore, the results obtained by finite volume simulations will be compared with those obtained by experimental tests with isothermal upsetting. Given that in these last few years there has been a growing interest in obtaining mechanical components from submicrometric and/or nanometric structure materials which have been previously-processed by severe plastic deformation (SPD), this present research work deals with the determination of absolute critical damage for the abovementioned alloys once they have been ECAP (Equal Channel Angular Pressing) processed. This is considered to be of interest since it could allow the prediction of optimal processing conditions in advance. Graphical abstract: Highlights: Critical damage in AA5754, AA5083 and AA3103 is studied before and after ECAP processing. Isothermal forging of ECAP billets and FV simulations are performed. Experimental measurements are carried out in order to confirm the FV results. From this study, it is possible to predict the formation of cracks before the material is forged.